Zoophilia in a Patient with Frontotemporal Dementia - Othman, Zahiruddin; Razak, Asrene Abd; Zakaria, Rahimah (Japan International Cultural Exchange Foundation, 2014)
Objective: A 65-year-old divorced man who presented with a 4-year history of personality and behavioural changes with inappropriate sexual behaviour was studied. Result: Cognitive impairment was indicated by low scores in MMSE and RUDAS. Neuropsychological assessment showed poor melokinetic ability, delayed response, personality change and, poor visual learning and memory signifying frontal lobe with predominantly right temporal deficits. CT brain showed multifocal cerebellar infarction and old right occipital infarct. However, brain MRI was not done as the patient could not afford it. Conclusion: A patient with bvFTD and hypersexuality is at risk of zoophilia if they also have the traditional risk factors of zoophilia such as low education, residing in a rural area and lack of opportunities to have sex with human partners.